Digitization of Archival Data and Metadata in Archaeology: The Case of Ancona - Eleonora Iacopini (Proceedings)
During the development of the digital archaeological map of the city of Ancona, in the Marche region, around 12,000 files were digitized relating to the documents associated with the individual archaeological contexts, coming from the administrative archive, the historical archive, the drawing archive, excavation diaries, and all of the scientific documentation associated with them. Given the amount of data and their importance from an information point of view, to prevent them from remaining as “silent” documents, it was envisaged to associate each of them with a metadata system based on the Dublin Core Metadata Initiative (DCMI) standard.